Broadband Entrainment of Striatal Low-Threshold Spike Interneurons - Morales, Juan C.; Higgs, Matthew H.; Song, Soomin C.; Wilson, Charles J. (Frontiers in Neural Circuits, 2020)
Striatal interneurons and projection neurons are differentially tuned to spectral components of synaptic input signals, and this is especially apparent in their responses to oscillations. The broad frequency tuning of spike responses in somatostatin/NPY-expressing low threshold spike (LTS) interneurons sets them apart from other GABAergic interneurons in the striatum as well as from the spiny projection (SP) neurons. The mechanism of LTS interneuron spiking resonance was unrelated to its membrane impedance resonance; abolition of membrane impedance resonance did not alter the spiking resonance. A comparison of the phase resetting curves (PRCs) and spiking resonance profiles of LTS interneurons and SP neurons revealed a relationship between the frequency sensitivity of the neurons and the spectral components of their infinitesimal PRCs. Sine wave input currents could control spike timing in SP neurons and LTS interneurons only to the extent that their PRCs contained Fourier modes of corresponding frequency. LTS interneurons’ PRCs contain larger high-frequency components, endowing the neurons with enhanced responses to input frequencies faster than the cells’ autonomous firing rates. This enables the LTS cells to be entrained by frequency components of the input signal to which SP neurons are less responsive. In addition to its effects on firing rate, striatal feedforward inhibition by LTS interneurons may regulate the entrainment of SP neurons by oscillatory afferents.